Accountant Students’ Error In Writing: A Conceptual FRAMEWORK - Muddin, Ajwan (Peneliti.net, 2025)
This descriptive quantitative: were collected by tests: pretest and posttest. To know the instrument used in (Pre-test) and (Post-test) is valid and reliable; the researcher tried out the test. After the data have been collected on January to April 2024, the students of class F5 belong to experimental group while the students of class F4 belong to control group. Both classes were given pre-test at the beginning. Then, the students of experimental group were taught writing while the control group was taught without. It can be seen from the result of test. The average score increases writing narrative from mean 527 in 29 students’ from F5 as experimental and the average score F4 writing narrative is 522 from 29 students’. Meanwhile after treatment and the students’ writing narrative the score class F5 from 29 students’ got 820 from experimental. And then the score students’ writing narrative in class control F4 scores 810 from 29 students’ in writing narrative text. it can be seen that there is significant increase of experimental class to the students’ in writing ability. On the other words, the experimental class can be significant improvement in their learning writing ability and The hypothesis of testing shows that the score of the experimental class . it was founded that there is significant different between the result of the teaching and learning. It can be seen that the value of p is 0.000 lower than the value of the significant level 5% or 0.000 < 0.05 that get in the result of analysis